SINERGI PANGKALAN TENTARA NASIONAL INDONESIA ANGKATAN UDARA DAN BANDARA HALIM PERDANAKUSUMA MENGANTISIPASI ANCAMAN MILITER - Roni Wijaya (Strategi Pertahanan Udara, 2022)
The existence of the air base often intersects with the airport. This condition needs to be understood because it is known that the Indonesian Air Force base is not only used for defense but also for civil or commercial aviation, namely the Civil Inclave Airport as happened at Halim Perdanakusuma. The existence of the Halim Perdanakusuma Air Force Base and Halim Perdanakusuma Airport which are in one room is certainly not an easy matter, moreover it only has one runway that is used together where each has its own orientation, as it is known that the Air Base has a concern for building defense bases while The airport is oriented towards commercial flights. Conditions are getting more difficult with increasingly complex dynamics of threats so that constructive efforts are needed in the form of anticipating military threats and aviation safety. The research method used is a qualitative method with a phenomenological research design. The data obtained from the specified informants were then analyzed using qualitative techniques. From this study it was concluded that 1) the implementation of base defense at Halim Perdanakusuma AFB in anticipating military threats had not been carried out optimally, 2) the implementation of flight operations at Halim Perdanakusuma Airport in anticipating flight safety referring to existing provisions, and 3) synergy between Halim Perdanakusuma AFB and Halim Perdanakusuma Airport in anticipating military threats and aviation safety have not been implemented properly.Keywords: synergy, base defense, flight operations, military threats, aviation safety